PENDEKATAN METODE SERVQUAL DAN KLASTER FUZZY K-MEANS UNTUK MENGANALISIS INDEKS KEPUASAN NASABAH BANK X - Dewi Erliana; Mustafid Mustafid; Abdul Hoyyi (Jurnal Gaussian, 2014)
Servqual (service quality) is a method for measuring the service quality of each dimension attribute. Servqual dimensions include tangibles, empathy, responsiveness, reliability, and assurance. Cluster analysis is a technique for classifying objects that have the same characteristics in a relatively homogeneous group. One method of cluster is Fuzzy k-Means (FKM). Classification object with FkM, the existence each data point in a cluster is determined by the degree of membership. Determination of the optimum number of clusters using the accuracy measure Xie Beni index (XB). XB index calculation depends on the objective function or distance data to each cluster center, the distance between the center of the cluster, and weighted (fuzzifier). Based on the optimum number of clusters, then will be calculated percentage of Customer Satisfaction Index (CSI). This research is based on a case Bank X customers through questionnaires of customer satisfaction based on the servqual dimension. Result of the research showed the optimum number of cluster 4 and weight 1.1. Customers in cluster 1 was 84.36 % very satisfied with most of the service quality Bank X. Customer in cluster 2 was 72.79 % satisfied, but they think there was nothing more conspicuous of service quality in Bank X. Customer in cluster 3 are satisfied with the value of 77.66 % satisfaction primarily to the ease in submitting a complaint.